Back to Agora - Elena Maria MINEA (Transylvanian Review of Administrative Sciences, 2012)
One of the most important things that influence people’s happiness is the strength of their relationship with others: feeling close to and valued by others is a fundamental human need and the strength of our communities also depends on the connections and relations that people have within them. Appearing and evolving along with human communities, public spaces were the scene of many manifestations of the community, a place of conviviality, of spirituality – in all its forms – a religious, administrative and legal landmark. Urban public spaces are those where all the processes related to peoples existence take place and, especially, peoples’ cohabitation. These places are a reflection of the social structure, of the level of development and computer technology, not a flat, clean and shiny surface. The changing face of cities starts as well from the public space.